Micronized milo, urea and prairie hay for growing beef heifers - K. Bolsen; J. Oltjen; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1977)
Twenty-four individually fed heifers were used 1n two heifer trials to evaluate four combinations of micronized or dry-rolled milo and soybean meal or urea supplements 1n prairie hay growing rations. Feeding 4 to 5 lbs. of micronized milo produced an average of 17% faster and 16% more efficient gains than feeding 4 to 5 lbs. of dry-rolled milo.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen' s Day; 1977; Beef; Milo; Urea; Prairie hay; Heifers